Congenital Leukemia: A Rare Cause of Blueberry Muffin Rash - Curado, Ana Dias (2022)
Congenital leukemia is an extremely rare disease occurring within the first 28 days of life. The disease prognosis is poor with high mortality rates. We describe a case of congenital acute monocytic leukemia in a female infant whose disease underwent rapid progression and culminated in death due to multiple organ failure. Our patient presented at birth with leukemia cutis, hepatomegaly, and abnormal neurological examination. She also had evidence of cardiac and respiratory dysfunction. Laboratory results revealed severe anemia, hyperleukocytosis with monocytic predominance, coagulopathy, and findings consistent with tumor lysis syndrome. The autopsy showed diffuse multiorgan infiltration by acute monocytic leukemia. Congenital leukemia has distinctive clinical presentations which make it a diagnostic and therapeutic challenge. We aimed to draw attention to this rare disease and its differential diagnosis with other common causes of blueberry muffin rash associated with hepatosplenomegaly and leukocytosis.